2013
DOI: 10.1165/rcmb.2012-0052oc
|View full text |Cite
|
Sign up to set email alerts
|

Radical-Containing Ultrafine Particulate Matter Initiates Epithelial-to-Mesenchymal Transitions in Airway Epithelial Cells

Abstract: Environmentally persistent free radicals (EPFRs) in combustiongenerated particulate matter (PM) are capable of inducing pulmonary pathologies and contributing to the development of environmental asthma. In vivo exposure of infant rats to EPFRs demonstrates their ability to induce airway hyperresponsiveness to methacholine, a hallmark of asthma. However, the mechanisms by which combustionderived EPFRs elicit in vivo responses remain elusive. In this study, we used a chemically defined EPFR consisting of approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 53 publications
1
88
1
Order By: Relevance
“…This results in surface-stabilized, environmentally persistent free radicals (EPFR), which continue to exist in ambient air from hours to months, and can last at least 12 h in biological fluids. In laboratory animals and human lung cell lines they have been shown to cause the increased oxidative stress resulting in regeneration of reactive oxygen species (ROS) in biological systems, and associated with cancer, pulmonary and other diseases [62,63]. The formation of potentially toxic particulates, polycyclic aromatic hydrocarbons, and isocyanates, and their distribution between gas phase and solid phase for different building material fires has been investigated [47].…”
Section: Assessment Of Fire Toxicitymentioning
confidence: 99%
“…This results in surface-stabilized, environmentally persistent free radicals (EPFR), which continue to exist in ambient air from hours to months, and can last at least 12 h in biological fluids. In laboratory animals and human lung cell lines they have been shown to cause the increased oxidative stress resulting in regeneration of reactive oxygen species (ROS) in biological systems, and associated with cancer, pulmonary and other diseases [62,63]. The formation of potentially toxic particulates, polycyclic aromatic hydrocarbons, and isocyanates, and their distribution between gas phase and solid phase for different building material fires has been investigated [47].…”
Section: Assessment Of Fire Toxicitymentioning
confidence: 99%
“…Fibrosis can also result from epithelial to mesenchymal transition [21]. It was very recently demonstrated that ultrafine particles containing radicals initiate such a transition in airway epithelial cells [22]. Our further investigations will explore such a possibility.…”
Section: Effect Of Epithelial Secretion On Fibroblast Proliferation Imentioning
confidence: 90%
“…As previously noted, the deposition of particulate matter is affected by the underlying status of the airways (Kim and Kang, 1997). This includes particulate-induced conditions, already described, as well as conditions such as nonallergic asthma and other disorders that predispose an individual to bronchial hypersensitivity (Nel et al, 1998;Hamada et al, 2000;Nicolai, 2002;Peden, 2002;Weisel, 2002;Whitekus et al, 2002;Hao et al, 2003;Ryman-Rasmussen et al, 2009;Scarino et al, 2012;Thevenot et al, 2012). For example, beryllium sensitivity is believed to be the result of a genetic polymorphism (Santo Tomas, 2009).…”
Section: Pulmonary Tissue Repair Mechanismsmentioning
confidence: 97%